Influence of Positive and Threatened Awe on the Attitude Toward Norm Violations - Sawada, Kazuki; Nomura, Michio (Frontiers in Psychology, 2020)
Awe is an emotional response to vast stimuli needing for accommodation. Although several studies have revealed that awe led to more ethical attitudes toward one’s own behavior and to generosity toward people in general, it is unclear whether and how the two types of awe―positive and threatened―influence one’s attitude toward others’ social norm violations. In the current study, we examined the influence of these types of awe on tolerance toward deviators’ behavior by using a pre-post design and a scenario task within the Japanese population. The findings indicated that positive awe increased the tolerance of others’ norm violations, while threatening awe did not.